Anti-proliferative effect of Trigona honey on MCF-7 - Abd Rahman Hayati; Masniza Muhamad Lasim; Mohamed Adel MAR Elkadi; Nur Syahrina Binti Rahim; Asral Wirda Ahmad Asnawi; Nur Fariha Mohd Manzor (College of Pathologists, 2024)
Introduction: The ability to proliferate progressively is a crucial characteristic of cancer cells. A number of natural products including prophetic food were demonstrated to have an anti-proliferative effect on cancer cells. Trigona honey has received much attention for its anti-microbial and anti-oxidant properties. The anti-proliferative effect of this honey on cancer cells however, is yet to be discovered. Objective: The aim of this study is to investigate the anti-proliferative effect of Trigona honey on MCF-7 cells. Materials & Methods: MCF-7 cells were cultured in basal medium DMEM-F12, containing 10% fetal bovine serum, 1% antibiotic antimycotic and 1% glutamax. Upon 80% confluence in 96 well plate, used media were replaced with basal media enriched with different concentrations (v/v) of Trigona itama honey; 0, 0.049, 0.195, 0.78, 3.125, 12.5 and 25. Proliferation of MCF-7 cells after 24 and 72 hours were measured by WST assay. Higher absorbance reading denotes higher proliferation rate. Results: MCF-7 cells treated with Trigona honey-enriched media showed consistent reduction in cell proliferation after 24 and 72 hours. Discussion & Conclusion: These preliminary findings show a promising effect of Trigona honey as an anti-cancer agent through its anti-proliferative effect.